Տրանսլիտը և հայ ժողովրդի ինքնության պահպանումը - Հ. Հ. Հովհաննիսյան (ՀՀ ԳԱԱ հրատ.)
В основном представители армянских диаспор не умеют читать по-армянски в силу сложности современного армянского алфавита, а также широкого использования английского алфавита в компьютерных сообщениях и телефонных SMS на армянском языке. С этой целью предлагается еще один официальный алфавит–компьютерный армянский алфавит на основе английского алфавита. Most people in the Armenian Diaspora cannot read Armenian and use the English alphabet for text messaging in Armenian. It seems appropriate to develop a new official alphabet based on an English one for computer correspondence in Armenian. Such an alphabet will help all the Armenians access the Armenian language, literature, and culture.
Keywords: Philology; Linguistics; Language and Literature